The Last Wolf - Morpurgo M. Michael (London, Corgi Yearling Books, 2003)
Robbie McLeod is on the run from the English Redcoats in the Highlands. On his travels he finds a wolf cub, near a sign proclaiming the killing of the last wolf in Scotland. Robbie adopts the orphaned cub and a friendship grows between them. But can they find a new freer life in America?